Investigation of Baseline Iron Levels in Australian Chickpea and Evaluation of a Transgenic Biofortification Approach - Tan, Grace Z. H.; Das Bhowmik, Sudipta S.; Hoang, Thi M. L.; Karbaschi, Mohammad R.; Long, Hao; Cheng, Alam; Bonneau, Julien P.; Beasley, Jesse T.; Johnson, Alexander A. T.; Williams, Brett; Mundree, Sagadevan G. (Frontiers in Plant Science, 2018)
Iron deficiency currently affects over two billion people worldwide despite significant advances in technology and society aimed at mitigating this global health problem. Biofortification of food staples with iron (Fe) represents a sustainable approach for alleviating human Fe deficiency in developing countries, however, biofortification efforts have focused extensively on cereal staples while pulses have been largely overlooked. In this study we describe a genetic engineering (GE) approach to biofortify the pulse crop, chickpea (Cicer arietinum L.), with Fe using a combination of the chickpea nicotianamine synthase 2 (CaNAS2) and soybean (Glycine max) ferritin (GmFER) genes which function in Fe transport and storage, respectively. This study consists of three main components: 1) the establishment for baseline Fe concentration of existing germplam, 2) the isolation and study of expression pattern of the novel CaNAS2 gene, and 3) the generation of GE chickpea overexpressing the CaNAS2 and GmFER genes. Seed of six commercial chickpea cultivars was collected from four different field locations in Australia and assessed for seed Fe concentration. The results revealed little difference between the cultivars assessed, and that chickpea seed Fe was negatively affected where soil Fe bioavailability is low. The desi cultivar HatTrick was then selected for further study. From it, the CaNAS2 gene was cloned and its expression in different tissues examined. The gene was found to be expressed in multiple vegetative tissues under Fe-sufficient conditions, suggesting that it may play a housekeeping role in systemic translocation of Fe. Two GE chickpea events were then generated and the overexpression of the CaNAS2 and GmFER transgenes confirmed. Analysis of nicotianamine (NA) and Fe levels in the GE seeds revealed that NA was nearly doubled compared to the null control while Fe concentration was not changed. Increased NA content in chickpea seed is likely to translate into increased Fe bioavailability and may thus overcome the effect of the bioavailability inhibitors found in pulses; however, further study is required to confirm this. This is the first known example of GE Fe biofortified chickpea; information gleaned from this study can feed into future pulse biofortification work to help alleviate global Fe deficiency.